Combination Therapy with Ibrexafungerp (Formerly SCY-078), a First-in-Class Triterpenoid Inhibitor of (1→3)-β-d-Glucan Synthesis, and Isavuconazole for Treatment of Experimental Invasive Pulmonary Aspergillosis - Petraitis, Vidmantas (Antimicrob Agents Chemother, 2020)
Ibrexafungerp (formerly SCY-078) is a semisynthetic triterpenoid and potent (1→3)-β-d-glucan synthase inhibitor. We investigated the in vitro activity, pharmacokinetics, and in vivo efficacy of ibrexafungerp (SCY) alone and in combination with antimold triazole isavuconazole (ISA) against invasive pulmonary aspergillosis (IPA). The combination of ibrexafungerp and isavuconazole in in vitro studies resulted in additive and synergistic interactions against Aspergillus spp. Plasma concentration-time curves of ibrexafungerp were compatible with linear dose proportional profile. In vivo efficacy was studied in a well-established persistently neutropenic New Zealand White (NZW) rabbit model of experimental IPA. Treatment groups included untreated control (UC) rabbits and rabbits receiving ibrexafungerp at 2.5 (SCY2.5) and 7.5 (SCY7.5) mg/kg of body weight/day, isavuconazole at 40 (ISA40) mg/kg/day, or combinations of SCY2.5+ISA40 and SCY7.5+ISA40. The combination of SCY+ISA produced an in vitro synergistic interaction. There were significant in vivo reductions of residual fungal burden, lung weights, and pulmonary infarct scores in SCY2.5+ISA40, SCY7.5+ISA40, and ISA40 treatment groups versus those of the SCY2.5-treated, SCY7.5-treated, and UC (P < 0.01) groups. Rabbits treated with SCY2.5+ISA40 and SCY7.5+ISA40 had prolonged survival in comparison to that of the SCY2.5-, SCY7.5-, ISA40-treated, or UC (P < 0.05) groups. Serum galactomannan index (GMI) and (1→3)-β-d-glucan levels significantly declined in animals treated with the combination of SCY7.5+ISA40 in comparison to those of animals treated with SCY7.5 or ISA40 (P < 0.05). Ibrexafungerp and isavuconazole combination demonstrated prolonged survival, decreased pulmonary injury, reduced residual fungal burden, and lower GMI and (1→3)-β-d-glucan levels in comparison to those of single therapy for treatment of IPA. These findings provide an experimental foundation for clinical evaluation of the combination of ibrexafungerp and an antimold triazole for treatment of IPA.